The effects of facial expressions on judgments of others when observing two-person confrontation scenes from a third person perspective - Ueda, Yoshiyuki; Yoshikawa, Sakiko (Frontiers in Psychology, 2022)
When building personal relationships, it is important to select optimal partners, even based on the first meeting. This study was inspired by the idea that people who smile are considered more trustworthy and attractive. However, this may not always be true in daily life. Previous studies have used a relatively simple method of judging others by presenting a photograph of one person’s face. To move beyond this approach and examine more complex situations, we presented the faces of two people confronted with each other to participants and asked them to judge them from a third-person perspective. Through three experiments, participants were asked to judge which of the two persons was more appropriate for forming alliances, more trustworthy, or more attractive, respectively. In all experiments, images were shown for a short (500 ms) or a long time (5 sec). In all three experiments, the results showed that participants were more likely to choose persons with happy faces than those with neutral, sad, or angry faces when the image presentation was short. Contrarily, the facial expressions did not affect those judgments when the image presentation was long. Instead, judgments were correlated with personality estimated from the model’s neutral face in a single-person presentation. These results suggest that although facial expressions can affect the judgments of others when observing two-person confrontations from a third-person perspective, when participants have more time to elaborate their judgments, they go beyond expressions.